Enhancing lettuce (Lactuca sativa L.) production with plant growth-promoting rhizobacteria - Gafur, Muzna Ardin Abdul; Sangadji, Zulkarnain; Riskawati, Riskawati; Mayor, Felia Imelda (Jurnal Ilmiah Pertanian, 2024)
Cultivating lettuce (Lactuca sativa L.) using plant growth-promoting rhizobacteria (PGPR) in Sorong Regency is uncommon, limiting production despite the high market potential. This study aims to evaluate the effect of PGPR and identify the optimal concentration to improve lettuce growth and yield. The research was conducted in Malawili Village, Sorong Regency, Indonesia, using a randomized block design (RBD) with four treatments: P0 (7.5 mL/L), P1 (10.5 mL/L), P2 (13.5 mL/L), and P3 (16.5 mL/L). Results revealed that PGPR significantly enhanced growth parameters, including plant height, leaf number, fresh biomass weight, biomass weight per plot, fresh weight for consumption, and root length. Among all treatments, 13.5 mL/L (P2) demonstrated the best outcomes, with plant height reaching 14.6 cm, fresh biomass weight of 633.3 g, and root length of 9.6 cm. PGPR application at appropriate concentrations effectively stimulates growth, increases nutrient uptake, and improves yield. These findings underline PGPR's potential to enhance lettuce production sustainably.